2017
DOI: 10.1016/j.wneu.2017.03.001
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality-Associated Characteristics of Patients with Traumatic Brain Injury at the University Teaching Hospital of Kigali, Rwanda

Abstract: OBJECTIVE Traumatic brain injury (TBI) is a leading cause of death and disability. Patients with TBI in low and middle-income countries have worse outcomes than patients in high-income countries. We evaluated important clinical indicators associated with mortality for patients with TBI at University Teaching Hospital of Kigali, Kigali, Rwanda. METHODS A prospective consecutive sampling of patients with TBI presenting to University Teaching Hospital of Kigali Accident and Emergency Department was screened for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
4
19
1
1
Order By: Relevance
“…6 In Kigali, the capital city of Rwanda, TBIs are responsible for approximately 16% of injuries presenting to the University Teaching Hospital of Kigali (CHUK), with severe TBI patients having a mortality rate as high as 58%. 7,8 This made head injury the most common diagnosis in injury-related deaths in 2012. 8 The most common etiology of TBIs was found to be road traffic incidents (RTIs), which commonly involved motorcyclists and pedestrians.…”
Section: Introductionmentioning
confidence: 99%
“…6 In Kigali, the capital city of Rwanda, TBIs are responsible for approximately 16% of injuries presenting to the University Teaching Hospital of Kigali (CHUK), with severe TBI patients having a mortality rate as high as 58%. 7,8 This made head injury the most common diagnosis in injury-related deaths in 2012. 8 The most common etiology of TBIs was found to be road traffic incidents (RTIs), which commonly involved motorcyclists and pedestrians.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries in Rwanda are associated with significant morbidity and mortality 5,6. Past studies in Rwanda have shown that most trauma victims are young men 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries in Rwanda are associated with significant morbidity and mortality 5,6. Past studies in Rwanda have shown that most trauma victims are young men 5,6. Road traffic accidents (RTA), especially those involving motorcycles, were the most common mechanism for adults, while children were frequently injured as pedestrians 3.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies conducted in neighboring regions of Tanzania have found even higher proportions of surgery recipients among moderate and severe TBI patients [ 36 , 37 ]. Similar studies in Rwanda and Uganda have also documented higher rates of surgery among TBI patient cohorts [ 11 , 62 ]. It is possible that we observed a lower provision of surgery among our sample because patients in our registry did not need surgery.…”
Section: Discussionmentioning
confidence: 57%